Efficacy of Metamifop against grassy weeds in direct-sown rice (Oryza sativa) and its impact on succeeding crop - SAHA, SANJOY; MUNDA, SUSHMITA (The Indian Journal of Agricultural Sciences, 2018)
Metamifop is an aryloxyphenoxypropionate herbicide that controls grassy weeds. Insufficient information is available on the dose of application of metamifop for post-emergence weed control. A field experiment was conducted during 2014-15 and 2015-16 at ICAR-National Rice Research Institute to determine the most effective dose of metamifop in direct-sown rice (Oryza sativa L.) and its impact in rice-rice cropping sequence. The treatments consisted of 4 doses of metamifop 10% EC at 75, 100, 150 and 200 g/ha along with oxyfluorfen 23.5% EC at 240 g/ha as standard check. Application of metamifop at 200 g/ha effectively controlled all the grassy weeds (weed control efficiency, 80-84%) except Leptochloa chinensis. Similar trend was observed with metamifop at 150 g/ha (weed control efficiency, 76-82%). Metamifop at 150 g/ha recorded 4.59 tonnes/ha grain yield and it was at par with metamifop applied at 200 g/ha (4.84 tonnes/ha). There was no negative effect of the herbicide treatments on the germination percentage, growth and yield of the succeeding rice crop in rice-rice cropping sequence. Therefore, metamifop 10% EC at 150 g/ha would be optimum recommendation for the control of grassy weeds in rice crop, considering the lower dose for reducing the herbicide load in the environment.